Pembuatan Sistem Informasi Berbasis Web di Desa Lieue Sebagai Media dalam Meningkatkan Kualitas Penyebaran Informasi dan Pelayananan Administrasi - Murti Raazi, Irfan; Wahyuni, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Community Service Lecture which was held in Lieue Village, Darussalam District, Aceh Besar District aims to increase literacy in the use and utilization of Information and Communication Technology (ICT). Therefore, Lieue Village still does not have a public information dissemination media that can be accessed by the community, where all information related to the village in some aspects still uses word of mouth system, this is very ineffective and the accuracy of information is low. Basically village development will follow the times in the process of supporting the quality of information delivery and village administration services required information technology-based media. The development of increasingly advanced information technology in a fast information system will show a tremendous impact on the pattern of people's lives. So that the author is encouraged to build a website-based information system so that it can be applied in Lieue Village to overcome the problems that have occurred so far. Thus, the existence of an information system in Lieue Village, the community can directly access various kinds of information presented and more effective administrative services. The system development uses the RAD approach SDLC method which includes requirements planning, design, and implementation.